EKSISTENSI PEMBELAJARAN BAHASA SANSKERTA PADA MADYAMA WIDYĀLAYA JÑANA DHARMA SASTRA DI DESA UMAJERO KECAMATAN BUSUNG BIU KABUPATEN BULELENG - Ketut Sukawiari; I Ketut Gunarta; I Putu Aryatnaya Giri (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Sanskrit is one of the classical languages that plays an important role in understanding the sources of Hindu teachings and preserving Hindu cultural and spiritual heritage. Madyama Widyālaya Jñana Dharma Sastra has made Sanskrit one of the local content subjects taught to students. This study aims to determine: (1) the existence of Sanskrit language learning at Madyama Widyālaya Jñana Dharma Sastra; (2) the factors that support and hinder Sanskrit language learning; and (3) the efforts undertaken to maintain the existence of Sanskrit language learning from the perspectives of Humanistic Learning Theory and Motivation Theory. This research employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, documentation, and literature study. The research informants consisted of the principal, Sanskrit language teacher, and students. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Sanskrit language learning at Madyama Widyālaya Jñana Dharma Sastra continues to exist and plays a significant role in enhancing students’ understanding of Hindu teachings, preserving Hindu cultural and spiritual heritage, and developing students’ religious character. The learning materials include Devanagari script, Sanskrit grammar, the Bhagavad Gita, and Subhasitam. Supporting factors include students’ learning motivation, interest in Hindu culture and teachings, teacher support, learning facilities, and a conducive school environment. Meanwhile, inhibiting factors include the complexity of the learning materials, limited learning resources, and differences in students’ abilities. Efforts to maintain the existence of Sanskrit language learning include the use of engaging teaching methods, provision of learning facilities and media, integration of Sanskrit into religious activities, giving rewards to students, improving teacher competence, and strengthening students’ intrinsic and extrinsic motivation.